Virtual-reality exposure treatment for first responder PTSD: a pilot investigation - Beidel, Deborah C.; Bowers, Clint A.; Newins, Amie. R.; Seaver, Christine; Rozek, David; McDaniel, Carole; Horning, Daniel R. (Frontiers in Virtual Reality, 2024)
There is increasing recognition that first responders’ exposure to multiple traumatic events puts them at risk for the development of emotional distress, including depression, substance misuse, posttraumatic stress disorder (PTSD), and suicide. Despite this increased risk and higher prevalence of PTSD and other trauma-related disorders, there are few data on treatment for first responders. This investigation describes the outcome of an intensive outpatient program (IOP), initially developed for military trauma, as applied to the treatment of first responders with PTSD. This treatment is unique in that it utilizes virtual reality to enhance the immersion into the exposure scene. Furthermore, we assessed the utility of both fixed-length and unbounded-length exposure sessions. The results indicate that the intervention was feasible to implement and did not produce iatrogenic effects. Participants reported significantly reduced symptoms of PTSD and related emotional distress, reduced disability, and improved daily functioning. These positive outcomes were maintained at 3-month follow-up. There was no difference in outcomes between the fixed- and unbounded-length sessions. The results are discussed in terms of the needs of first responders to have access to efficacious, short-term interventions that allow them to quickly return to their profession.